P327 Long-term effectiveness of ustekinumab in refractory Crohn's disease: an Italian multicenter real-life study. (27th May 2021) - Scribano, M L; Aratari, A; Neri, B; Bezzio, C; Balestrieri, P; Falasco, G; Camastra, C; Pantanella, P; Monterubbianesi, R; Tullio, A; Saibeni, S; Papi, C; et al.
Abstract: Background: Ustekinumab (UST) is increasingly used in Italy for the treatment of refractory Crohn's disease (CD), however very few data concerning real-life experience has been reported. Therefore, the aim of this study was to assess the long-term effectiveness of UST in refractory CD patients treated in a large Italian cohort. Methods: A retrospective study was conducted in 5 Italian tertiary centers. All adult CD patients who started UST because of anti-tumor necrosis factor (TNF) failure were included. The co-primary outcomes were steroid-free clinical remission (defined as Harvey Bradshaw Index, HBI ≤4) at weeks 26 and 52. Secondary outcomes were changes in HBI score, changes in C-reactive protein (CRP) values, normalization of CRP (≤0.5 mg/dl) at weeks 8, 26, and 52, and adverse events. Categorical variables were expressed as frequency and percentage. Unpaired t -test was used to compare variables. A p -value <0.05 indicated statistical significance. Continuous variables were expressed as mean and standard deviation (SD), and median with interquartile range (IQR). Results: Between Nov 2018 and Feb 2020, 140 patients (51.4% male; median age 45.0 years, IQR 36.3-54.0; median disease duration 16.0 years, IQR 8.0-22.0) were included. The majority of patients had ileocolonic disease (L1, 38.6%; L2, 11.4%; L3, 50.0%) and an inflammatory phenotype (B1, 50.7%; B2, 31.0%; B3, 18.3%). All patients had previously been exposed to at least one anti-TNF agent, 27.1% to 2 anti-TNF agents, and 20.0% to vedolizumab . At inclusion 15.7% of patients received corticosteroids and 8.6% immunomodulators. All patients received an intravenous dose of 6 mg/kg, followed by subcutaneous administration of 90 mg every 8 (90%) or 12 weeks (10%) according to clinical judgment. The proportion of patients achieving steroid-free clinical remission was 61.0% and 64.2% at weeks 26 and 52 respectively. A significant decrease in the mean HBI was reported from baseline to week 8 (6.8 ± 3.6 vs 4.5 ± 3.1; p <0.001), week 26 (3.5 ± 2.9; p <0.001), and week 52 (3.1 ± 2.4; p <0.001). The mean CRP values was also significantly decreased from baseline to week 8 (4.6 ± 7.3 vs 2.8 ± 7.1; p <0.001), week 26 (1.7 ± 3.8; p <0.001), and week 52 (1.1 ± 2.2; p<0.001). At baseline 93 of 119 patients had high CRP value: a normal CRP value was observed in 34.9%, 37.8%, and 49.3% of patients at weeks 8, 26, and 52 respectively. Overall, 11 patients (7.9%) discontinued UST within 1 year: primary failure (n=2), secondary failure (n=6), adverse events (n=3: 2 allergic reactions, and 1 arthralgia). Conclusion: To our knowledge this is one of the largest Italian cohort followed up to 1 year, and the results confirm that UST is an effective and safe treatment in refractory CD patients.